Lung cancer staging: a concise update. Issue 5 (17th May 2018) - Rami-Porta, Ramón; Call, Sergi; Dooms, Christophe; Obiols, Carme; Sánchez, Marcelo; Travis, William D.; Vollmer, Ivan
Diagnosis and clinical staging of lung cancer are fundamental to planning therapy. The techniques for clinical staging, i.e . anatomic and metabolic imaging, endoscopies and minimally invasive surgical procedures, should be performed sequentially and with an increasing degree of invasiveness. Intraoperative staging, assessing the magnitude of the primary tumour, the involved structures, and the loco-regional lymphatic spread by means of systematic nodal dissection, is essential in order to achieve a complete resection. In resected tumours, pathological staging, with the systematic study of the resected specimens, is the strongest prognostic indicator and is essential to make further decisions on therapy. In the present decade, the guidelines on lung cancer staging of the American College of Chest Physicians and the European Society of Thoracic Surgeons are based on the best available evidence and are widely followed. Recent advances in the classification of the adenocarcinoma of the lung, with the definition of adenocarcinoma in situ, minimally invasive adenocarcinoma and lepidic predominant adenocarcinoma, and the publication of the eighth edition of the tumour, node and metastasis classification of lung cancer, have to be integrated into the staging process. The present review complements the latest guidelines on lung cancer staging by providing an update of all these issues. Lung cancer staging is a multidisciplinary activity that involves specialists in imaging, endoscopists, surgeons and pathologists at clinical and pathological staging http://ow.ly/z3M030jzmhN